PENGELOLAAN LABORATORIUM UNIT GAWAT DARURAT - J. Nugraha (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
The need for comprehensive and independent services in the emergency unit led to a need for a special laboratory organization inthe unit. The simple laboratory organization has a special character that has a rapid and an accurate result, but it only provides certainparameters, which related to emergency condition. In the emergency unit laboratory tests are preferred to support the procedure ofdiagnosis and clinical decisions rather than to ensure that definitive diagnosis can be continued later, when the patient was moved tothe ward. The test is chosen to support the diagnosis of diseases which requiring immediate treatment, such as myocardial infarction,stroke, emergency surgery preparation, the diagnosis of infection and electrolyte tests and blood gas analysis especially for critically illpatients. Back up instruments should be provided that can be operated anytime when there is congestion, an ideally means that willnot interrupted the services. The laboratory needs an emergency unit that can be served by means of a simple, fast, accurate thoroughtest, and it is cheap as well. The unit should also linked to LIS and HIS. So that the results can be known or accepted in all parts of thehospital. The advantage of a special laboratory emergency unit in this case may accelerate the time of service as well as saving energyand the communications will be more simple, compared to the central laboratory, and should be operated for 24 hours.